2022
DOI: 10.3390/ma15145022
|View full text |Cite
|
Sign up to set email alerts
|

Elastic Properties and Hardness of Mixed Alkaline Earth Silicate Oxynitride Glasses

Abstract: The incorporation of nitrogen as a second anion species into oxide glasses offers unique opportunities for modifying glass properties via changes in glass polymerization and structure. In this work, the compositional dependence of elastic properties and the nanoindentation hardness of mixed alkaline-earth silicate oxynitride glasses containing a high amount of nitrogen (>15 at.%, c.a. 35 e/o) were investigated. Three series of silicon oxynitride glass compositions AE–Ca–Si–O–N glasses (where AE = Mg, Sr, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Notwithstanding a non-negligible { P B pq } data scatter within each relatively small K –0.75 and 2.0–2.1 glass series, once considering both the M z + content ( x M ; eq ) and the CFS, a significant impact from the network modifier reservoir on the borate group intermixing becomes evident across the full BS glass ensemble. Focusing on the B [4] –O–B [4] linkages, the { P B 44 } set correlated well with the effective CFS defined by , (Tables and S5)­ yielding the following empirical best-fit expression which is displayed in Figure a. Notably, the exponent 0.425 ≈ 1/2 of eq (with uncertainty ±0.033) implies that the deviation from a perfect B [4] –O–B [4] avoidance ( P B 44 = 0) grows approximately as .…”
Section: Resultsmentioning
confidence: 67%
“…Notwithstanding a non-negligible { P B pq } data scatter within each relatively small K –0.75 and 2.0–2.1 glass series, once considering both the M z + content ( x M ; eq ) and the CFS, a significant impact from the network modifier reservoir on the borate group intermixing becomes evident across the full BS glass ensemble. Focusing on the B [4] –O–B [4] linkages, the { P B 44 } set correlated well with the effective CFS defined by , (Tables and S5)­ yielding the following empirical best-fit expression which is displayed in Figure a. Notably, the exponent 0.425 ≈ 1/2 of eq (with uncertainty ±0.033) implies that the deviation from a perfect B [4] –O–B [4] avoidance ( P B 44 = 0) grows approximately as .…”
Section: Resultsmentioning
confidence: 67%
“…Out of the alkaline‐earth bearing M–(Al)–Si–O–N glass families, those with M 2+ = {Ca 2+ , Mg 2+ } have received most attention, 7,9,11,13,19,26–29 but a few studies also targeted Sr 2+ and Ba 2+ bearing glasses 7,19,30–34 . The formation of Ca–Al–Si–O–N glasses and related ones have primarily been examined for specimens prepared by melting oxides and nitrides of Si and/or Al in N 2 atmosphere; then, a traditional melt‐quench procedure may produce glasses with N contents reaching up to ≈7 at.%, which corresponds roughly to ≈16 equivalent percent (eq.%) of N out of all anions (O and N) 5,11,19,21 .…”
Section: Introductionmentioning
confidence: 99%
“…25 e/o. Recently, few studies have reported that AE/RE–Si–O–N (where “AE” is alkaline-earth and “RE” is rare-earth) glasses can be formed by incorporating a metal modifier such as metal hydride or even pure metal in the reaction mixture rather than using metal oxides, as typically used with silicon nitride (Si 3 N 4 ) as the N source yielding oxynitride glasses, with N content of up to 60 e/o with exceptional thermal, mechanical, and optical properties [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%